Basic Frameworks of ICT in the Structure of Professional Standard for Teachers - Yarmakhov B.B; Sotnikova A.L; Patarakin E.D (Moscow State University of Psychology and Education, 2018)
The paper provides a detailed review of the issue of basic frameworks underlying the development of professional standards for teachers in the part referring to ICT competency. We focus on a case of designing an ecosystem of the ISTE association community which is based on the lifecycle of standards for students, educators, coaches, computer science educators and school administrators. We analyse the mechanism of transforming the ICT competency standards into educational policies on the basis of the approach proposed by UNESCO. Also, we explore the mechanisms of translating the frameworks of the teacher's ICT competency standards into national educational systems.